Diverse subtypes of astrocytes and their development during corticogenesis - Tabata, Hidenori (Frontiers in Neuroscience, 2015)
Astrocytes are one of the most abundant cell types in the mammalian central nervous system, and are known to have a wide variety of physiological functions, including maintenance of neurons, formation of the blood brain barrier, and regulation of synapse functions. Although the migration and positioning of neurons has been extensively studied over the last several decades and many aspects have been uncovered, the process underlying glial development was largely unknown until recently due to the existence of multiple subtypes of glia and the sustained proliferative ability of these cells through adulthood. To overcome these difficulties, new gene transfer techniques and genetically modified mice were developed, and have been gradually revealing when and how astrocytes develop during corticogenesis. In this paper, we review the diversity of astrocytes and summarize our knowledge about their production and migration.